“...Friend of My Youth”: Image of a Dog in the Lyrics of S. A. Yesenin - S. N. Pyatkin (Научный диалог, 2019)
The article examines the artistic and functional status of the image of a dog’s motive in Yesenin’s lyrics in the context of the idea of an organic unity of art and life, which largely determines the poet’s creative philosophy. Three poems are considered in which the image of a dog is the central figure of the text and the constructive basis of its ideological and artistic content: “Song of the Dog” (1915), “Son of a Bitch” (1924), and “Kachalov’s Dog” (1925). The analysis of the subject-figurative structure of each of the poems is carried out, while they selectively comment on individual elements of the poetics of the text, which contributes to a detailed understanding of the role of the studied image. In the analysis of “Songs about a Dog”, attention is drawn to the peculiarities of interaction in the text of image and expression plans, cinematography as the main extra-subjective form of author’s consciousness in the poem, and also to the functional heterogeneity of the lyrical narrative. When considering the work “Son of a bitch”, the emphasis is on the specifics of the space-time structure of the text, namely on the special movement of time initiated by the subject of speech - from an uncertain future to a certain past. When studying the poem “The Dog of Kachalov”, attention is focused on the distinctive features of his genre solution, which is characterized by a synthesis of various genre elements of lyrics: dedication, message, elegy, confession. It is argued that in all three poems the image of a dog serves as a mediator (guide), the semantic variations of which depend on the poetic context and come from the ontological relationship of the world of everyday ideas and the world of spiritual revelations of a person, which determines the main content of Yesenin's artistic philosophy.